Photon-Assisted Transport Through a Quantum Dot Side-Coupled to Majorana Bound States - Chi, Feng; He, Tian-Yu; Wang, Jing; Fu, Zhen-Guo; Liu, Li-Ming; Liu, Ping; Zhang, Ping (Frontiers in Physics, 2020)
Transmission function of a system composing of a quantum dot (QD) subjected to a photon field and side-coupled to a topological superconductor nanowire hosting a pair of Majorana bound states (MBSs) is calculated by using the non-equilibrium Green's function technique. We find that a series of photon-induced peaks emerge and are split by the coupling between the QD and the MBSs. Moreover, the peaks' height are suppressed to zero because the MBSs absorb (emit) the photon energy. Under this condition, the MBSs may be shifted to the non-zero energy mode, and thus provide another detection scheme for its existence which is quite different from the currently adopted ones depending on the zero-energy mode of the MBSs. In the presence of MBS-MBS overlaping, the central photon-assisted peaks in the transmission function reappear due to the fact that the photon absorbed (emitted) by one mode of the MBSs are subsequently emitted (absorbed) by another MBSs' mode. We also find that the positions of the additional peaks induced by the MBS-MBS overlaping in the presence of the photon field are quite different from the case of zero photon field.